Automatic fiscal stabilisers: Recent evolution and policy options to boost their effectiveness - Maravalle, Alessandro (OECD Publishing, 2020)
Building on the automatic fiscal stabilisers literature, this paper assesses how automatic stabilisers have evolved over the past two decades by analysing changes in the personal income tax and social benefit systems. In three-quarters of the 35 OECD countries analysed, indicators of the strength of automatic stabilisers (aggregate elasticities of household income after tax with respect to the cycle and aggregate net replacement rates) changed little or moderately over the past two decades, suggesting broadly stable automatic stabilisers of household disposable income. The paper discusses pros and cons of several policy options to strengthen automatic stabilisers in the current environment. The effectiveness and possible side effects, particularly related to disincentives to work, vary across policy options. Consequently, policy reform proposals should be carefully assessed in a country-specific context and take into account other important policy objectives of tax and benefit systems
Keywords: Economics